Using Visual Methods to Capture Embedded Processes of Resilience for Youth across Cultures and Contexts - Didkowsky, Nora (Canadian Academy of Child and Adolescent Psychiatry, 2010)
OBJECTIVES: We review the value of using visual data in a dialogue with youth, to reflect, explore and find language to better understand processes of resilience. METHODS: The argument is demonstrated with examples from the Negotiating Resilience Project (NRP): an international study of 16 youth which uses video recording a day in the life of youth participants, photographs produced by youth, and reflective interviews with the youth about their visual data. RESULTS: Three examples from the NRP are used to show the ways that visual methods can capture and elucidate previously hidden aspects of youth’s positive psychosocial development in stressful social ecologies. CONCLUSION: Incorporating images as research data can aid in understanding previously unarticulated constructions of youth resilience. When the researcher is reflexive about power dynamics and their role in co-constructing the research environment, visual methods have the potential to reduce power imbalances in the field, meaningfully engage youth in the research process, and help to overcome language barriers.